Development of Encyclopedia Learning Media Based on Local Vegetables as An Innovative Biology Learning Resource - Sofianti, Mery; Sunandar, Ari; Qurbaniah, Mahwar (Jurnal Kependidikan : Jurnal Hasil Penelitian dan Kajian Kepustakaan di Bidang Pendidikan, Pengajaran, dan Pembelajaran, 2024)
This research aims to produce an encyclopedia learning media that is both valid and practical for improving students’ understanding of biodiversity material. The research utilized a modified 4-D development model, streamlined into 3-D, which included the stages of Define, Design, and Develop. The instruments used comprise interviews and documentation. Data analysis included validation of the encyclopedia’s development and analysis of student responses to the developed media. The results from the validation tests and student responses indicated positive outcomes. Media experts rated the validation at 95.83% (very valid), material experts at 84.28% (very valid), and language experts at 83.33% (valid). Students who responded to the small-scale trial were very good, scoring 92.18% (very valid), while those who responded to the large-scale trial were also very good, at 91.03% (very valid). In conclusion, the validity results were very positive and the response outcomes were highly favorable. Thus, the encyclopedia media is deemed valid for use by educators and students in the biodiversity learning process.